The Effect Of Lactation Massage On Breast Milk Production In Breastfeeding Mothers - Herlina, Herlina; Aprilia Wardani, Riska (Universitas Islam Lamongan, 2023)
Breastfeeding is a proven way to make babies healthier and help them grow well. Exclusive breastfeeding as a baby can reduce the risk of stunting. Breastfeeding is the process of giving milk to babies with breast milk (ASI) from the mother's breasts. The success of exclusive breastfeeding is greatly influenced by the smooth production of breast milk from the beginning of the breastfeeding period According to 2021 Basic Health Research (RISKESDAS) data, 52.5 percent – or only half of the 2.3 million babies aged less than six months – are exclusively breastfed in Indonesia, or a decrease of 12 percent from the figure in 2019. Breastfeeding initiation rate Early childhood (IMD) also decreased from 58.2 percent in 2019 to 48.6 percent in 2021. The main reason babies are never breastfed is because breast milk does not come out or is not smooth at the start of the breastfeeding period (65.7%) babies aged 0- 5 months (33.3%) have been given food with the largest type of food (84.5%) namely formula milk. The East Java Central Statistics Agency (BPS) recorded that in 2022 the percentage of babies aged up to 6 months who received exclusive breast milk was 69 .72%. Plus, the percentage of new babies born who received Early Breastfeeding Initiation (IMD) was 69.22%. This type of research is quasi-experimental with quantitative research methods. This research uses a pre-post test pst test without control group design. The population in this study were all 20 breastfeeding mothers in Sooko Village. Data collection instruments used checklists/Standard Operating Procedures (SOP) for lactation massage and questionnaire sheets as well as breast milk expenditure observation sheets. The results of breast milk production are measured using a breast pump and measured using a measuring cup. From the results of the paried t-test, a significance of 0.000 <0.05 was obtained, so it can be concluded that there is an influence of lactation massage on breast milk production in breastfeeding mothers. Key words: Lactation massage, breast milk, breastfeeding mothers